2012
DOI: 10.1177/1470320312456328
|View full text |Cite
|
Sign up to set email alerts
|

Early changes of hypothalamic angiotensin II receptors expression in gestational protein-restricted offspring: effect on water intake, blood pressure and renal sodium handling

Abstract: The current study examines changes in the postnatal hypothalamic angiotensin receptors by maternal protein restriction (LP), and its impact on in uteri programming of hypertension in adult life. The data show that LP male pup body weight was significantly reduced when compared to that of control (NP) pups. Also, immunoblotting analysis demonstrated a significantly decreased expression of type 1 AngII receptors (AT1 R ) in the entire hypothalamic tissue extract of LP rats at 12 days of age compared to age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Since these initial discoveries, most intrinsic components of the RAS, including angiotensinogen, angiotensin, and converting enzymes, have been well described and demonstrated in different areas of the central nervous system (CNS). 2,3 Notably, most previous studies in this field have focused on the central and peripheral angiotensin receptors and their roles in prenatal imprinting. The challenge for all of us is to understand in depth the mechanisms by which antenatal stress may alter normal neurophysiology of the brain RAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these initial discoveries, most intrinsic components of the RAS, including angiotensinogen, angiotensin, and converting enzymes, have been well described and demonstrated in different areas of the central nervous system (CNS). 2,3 Notably, most previous studies in this field have focused on the central and peripheral angiotensin receptors and their roles in prenatal imprinting. The challenge for all of us is to understand in depth the mechanisms by which antenatal stress may alter normal neurophysiology of the brain RAS.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine Impact of taurine supplementation on blood pressure in gestational proteinrestricted offspring: Effect on the medial solitary tract nucleus cell numbers, angiotensin receptors, and renal sodium handling malnutrition has been known to induce alterations in the development of several tissues, among which are the CNS. 3 The role of the CNS in the control of blood pressure and hydrosaline homeostasis has been demonstrated by several studies. 4,5 Also, the central role of the RAS in the control of blood pressure and hydroelectrolyte homeostasis has been widely demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanisms are still unclear, the association between maternal undernutrition and hormonal dysfunction has been proposed to induce intrauterine fetal programming. Studies have shown that excessive levels of fetal glucocorticoids may impair brain development, affect behavior and delay cognitive and intellectual functions later in life both in humans and animal models (Johnson et al, 1981;Uno et al, 1990Uno et al, , 1994Szuran et al, 2000;Antonow-Schlorke et al, 2001;Matthews, 2001;Antonow-Schlorke et al, 2003;French et al, 2004;Karemaker et al, 2008;Weinstock, 2008;Seckl, 2008;de Lima et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, altered expression of AT1r in areas of the brain involved in the regulation of blood pressure has been found in protein-restricted offspring (Pladys et al, 2004;de Lima et al, 2013). This change is probably associated with the autonomic changes found in these animals.…”
Section: Renin-angiotensin Systemmentioning
confidence: 93%